LERMOYEZ SYNDROME: A LITERATURE REVIEW - Bedaque, Henrique; Yasmim Barros Silveira; Rayane Bezerra Freitas; José Diniz Júnior (JOURNAL OF SURGICAL AND CLINICAL RESEARCH, 2024)
INTRODUCTION: Lermoyez Syndrome is considered a rare pathology of unknown etiology, whose clinical picture includes hypoacusis, tinnitus and vertigo, similar to Ménière's Disease, differing from the latter due to the improvement in auditory acuity during the vertigo crisis. GOAL: To review the most up-to-date articles on Lermoyez Syndrome, given its relevance for a full understanding of otoneurological complaints. METHODS: Literature review of articles published in the last 30 years, in English, Portuguese and Spanish, using the keyword “Lermoyez syndrome” in the MEDLINE, PUBMED and Scielo databases. RESULTS: Four articles were screened for full analysis. Three inferred that, although similar, there are intrinsic aspects in these patients, which distinguish their pathophysiology from those with Ménière's Disease. Audiometric tests seem to overlap the vestibular ones in terms of positive predictive value, both being widely detailed in the studies, highlighting the finding of improvement in the auditory threshold, after the vertigo episode, at lower frequencies. CONCLUSION: Although the clinical picture and audiological and vestibular findings of Lermoyez Syndrome are well described, the scarcity of studies about this disease makes it difficult to fully understand this pathology as well as its proper management.